Bed separation backfill to reduce surface cracking due to mining under thick and hard conglomerate: a case study. Issue 8 (21st August 2019) - Yin, Dawei; Chen, Shaojie; Li, Bo; Guo, Weijia
Abstract : After coal mining, the surface above a goaf may experience the discontinuous deformation under some special geological and mining conditions, such as surface cracking, surface step subsidence and collapse pits. Discontinuous deformation seriously threatens the safety of surface buildings and infrastructures. In this paper, the mechanism of discontinuous surface deformation and surface cracking due to coal mining under thick and hard conglomerate in the Huafeng coal mine was studied using a simulation test on similar materials. Bed separation backfill was then proposed to control surface cracking and to protect the Luli bridge. Because of lithological differences between the conglomerate and relatively weak red strata (beneath the conglomerate), the bed separation occurred between them with the advancement of the working face. When the bed separation span exceeded its breaking span, the conglomerate fractured, causing surface cracking of the downhill area and seriously damaging the stability of the Luli bridge. Three drilling holes were arranged along the strikes of the 1412 and 1613 working faces and nearly 387 000 m 3 of backfill materials (water, fly ash and gangue powder) were injected into the bed separation space to reduce or prevent fracturing of the conglomerate. The compacted backfill body supported the conglomerate and reduced the subsidence of the basin and surface 'rebound' deformation at the edge of the subsidence basin. Clay in the red strata expanded upon contact with water, and this further backfilled the bed separation zone and supported the conglomerate. The upper and lower structures and foundation of the bridge were reinforced using various methods. It was shown that bed separation backfill effectively controlled conglomerate movement and protected the bridge with a maximum subsidence of 251 mm. No obvious surface cracks were observed near the Luli bridge.